2018
DOI: 10.1063/1.5042148
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical nanostructure of CrCoNi film underlying its remarkable mechanical strength

Abstract: A CrCoNi medium entropy alloy thin film is fabricated using magnetron sputtering. It exhibits a unique hierarchical nanostructure, featuring (1) a high density of planar defects (mostly stacking faults plus a small number of twin boundaries), (2) a dual-phase configuration (a mix of face-centred-cubic and hexagonal-close-packed), and (3) vertically aligned, textured nanocolumns, each with a width of ∼100 nm. The hierarchical nanostructure in this study is original, especially for its dual phase combination, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Bearing these facts in mind, for the well-characterized CrCoNi MEA, the primary deformation mode is predicted to be DIMT at room temperature, which is further promoted at 77K. This result is in line with the experimental observations at both room and cryogenic temperatures [4,70]. For example, Miao et al found that in the equiatomic CrCoNi MEA hcp lamellae appear at large strain levels and its volume fraction increases at cryogenic temperature [4].…”
Section: Plastic Deformation Modessupporting
confidence: 71%
“…Bearing these facts in mind, for the well-characterized CrCoNi MEA, the primary deformation mode is predicted to be DIMT at room temperature, which is further promoted at 77K. This result is in line with the experimental observations at both room and cryogenic temperatures [4,70]. For example, Miao et al found that in the equiatomic CrCoNi MEA hcp lamellae appear at large strain levels and its volume fraction increases at cryogenic temperature [4].…”
Section: Plastic Deformation Modessupporting
confidence: 71%
“…At the atomic scale, typical STEM images of two columnar 'grains' (Fig. 1b, c [14,17], endowing it with ultrahigh hardness and unique deformation behavior [29].…”
Section: Hierarchical Nanostructures Of the Dual-phase Crconi Meamentioning
confidence: 99%
“…More recently, the design principles are dedicated to incorporating other strengthening mechanisms into this kind of novel alloys, such as microstructure modification [18][19][20], precipitation strengthening [21,22], ductile multicomponent intermetallic nanoparticles [23], and interstitial solid solution strengthening (by adding boron [24], carbon [25], nitrogen [26,27] and oxygen [28]), to push the property boundary of possibility apart from their inherent substitutional solid solution strengthening. Similarly, we successfully fabricated a nanostructured dual-phase (HCP and FCC) CrCoNi MEA using magnetron sputtering, which possesses ultrahigh nanohardness of~10 GPa obtained by nanoindentation that is much higher than that of conventional FCC structured counterpart [29,30]. It was revealed that this ultrahigh hardness originated from its unique hierarchical microstructures enabled by the special processes of magnetron sputtering [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure-induced hcp martensite was shown stable at ambient conditions after the release of the high pressure and transferring to the high temperature fcc phase after heating [108]. Additionally, Chen et al found the coexistence of the hcp and fcc phases in the epitaxial film where the hcp phase can reach very high fraction [110]. As discussed above, it is likely the large lattice friction stress [103,104] that prevents the spontaneous nucleation of hcp martensite in these alloys at room temperature, despite that the hcp structure is energetically more stable than the fcc one.…”
Section: Dftmentioning
confidence: 99%